The 8 and 5 kDa Fragments of Plasma Gelsolin Form Amyloid Fibrils by a Nucleated Polymerization Mechanism, while the 68 kDa Fragment is Not Amyloidogenic - Solomon, James P. (2009)
Familial amyloidosis of Finnish type (FAF), or gelsolin amyloidosis, is a systemic amyloid disease caused by a mutation (D187N/Y) in domain 2 of human plasma gelsolin, resulting in domain 2 misfolding within the secretory pathway. Upon passage through the Golgi, furin endoproteolysis within domain 2 occurs as a consequence of the abnormal conformations that enable furin to bind and cleave, resulting in the secretion of a 68-kDa C-terminal plasma gelsolin fragment (amino acids173–755, C68). The C68 fragment is cleaved upon secretion from the cell by membrane type 1 matrix metalloprotease (MT1-MMP), affording the 8 and 5 kDa fragments (amino acids 173–242 and 173–225, respectively) comprising the amyloid fibrils in FAF patients. Herein, we show that the 8 and 5 kDa gelsolin fragments form amyloid fibrils by a nucleated polymerization mechanism. In addition to demonstrating the expected concentration dependence of a nucleated polymerization reaction, the addition of preformed amyloid fibrils, or “seeds”, was shown to bypass the requirement for the formation of a high energy nucleus, accelerating 8 and 5 kDa D187N gelsolin amyloidogenesis. The C68 fragment can form small oligomers, but not amyloid fibrils, even when seeded with preformed 8 kDa fragment plasma gelsolin fibrils. Because the 68 kDa fragment of gelsolin does not form amyloid fibrils in vitro or in a recently published transgenic mouse model of FAF, we propose that administration of an MT1-MMP inhibitor could be an effective strategy for the treatment of FAF.